2022
DOI: 10.1177/16878132221114576
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady test technique of jet control with multi-parameter coupling

Abstract: In this paper, the jet control effect of air vehicle is studied, and a new multi parameter coupling unsteady test technique is established, which can ensure that the test model is consistent with the real air vehicle, and the jet is carried out under the condition of complete freedom and no support constraints, so that the wind tunnel test can better simulate the jet control effect of real air vehicle. The new technique overcomes the shortcoming that the previous jet test can only carry out unsteady flow field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A novel technique suitable for wind tunnel measurements, with additional points of contact between the model and the support sting, is proposed in Vuković et al 8 It is reported that transient starting and stopping loads can be reduced by more than 50%, which enables achieving higher Mach numbers in the working section. Another interesting example of an enhanced wind tunnel measuring technique is described in Xue et al 9 on a case of a jet controlled air vehicles. The peculiarities here are that the model is completely free, not constrained by any additional support, because a small volume high-pressure gas cylinder is incorporated directly into the model of the air vehicle, which enables the investigation of changes in model’s attitude and orientation with jet both on and off.…”
mentioning
confidence: 99%
“…A novel technique suitable for wind tunnel measurements, with additional points of contact between the model and the support sting, is proposed in Vuković et al 8 It is reported that transient starting and stopping loads can be reduced by more than 50%, which enables achieving higher Mach numbers in the working section. Another interesting example of an enhanced wind tunnel measuring technique is described in Xue et al 9 on a case of a jet controlled air vehicles. The peculiarities here are that the model is completely free, not constrained by any additional support, because a small volume high-pressure gas cylinder is incorporated directly into the model of the air vehicle, which enables the investigation of changes in model’s attitude and orientation with jet both on and off.…”
mentioning
confidence: 99%